Diffuse interstitial and multiple cavitary lung lesions due to Talaromyces marneffei infection in a non-HIV patient. (November 2015) - Li, H.R.; Xu, N.L.; Lin, M.; Hu, X.L.; Chen, J.H.; Chen, Y.S.; Cai, S.X.
Abstract: A 57-year-old man presented with unproductive cough and dyspnea for 6 months in Fujian Province, China. His misuse of a large amount of steroids (accumulated dose equivalent to 3530 mg prednisolone) resulted in Talaromyces marneffei infection. Chest computed tomographic scan revealed diffuse interstitial and multiple cavitary lung lesions. Treatment with amphotericin B combined with itraconazole resulted in total recovery, with marked regression of lung lesions.